2014
DOI: 10.15302/j-fase-2014005
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of the backfat thickness trait in two pig populations

Abstract: Backfat thickness is a good predictor of carcass lean content, an economically important trait, and a main breeding target in pig improvement. In this study, the candidate genes and genomic regions associated with the tenth rib backfat thickness trait were identified in two independent pig populations, using a genome-wide association study of porcine 60K SNP genotype data applying the compressed mixed linear model (CMLM) statistical method. For each population, 30 most significant single-nucleotide polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For example, Qiao et al (2015) performed a GWAS using a White Duroc × Erhualian F 2 intercross population and a Chinese Sutai population to reveal SNP and candidate genes related to growth and fatness traits, but no overlap of results was found in the 2 populations. Likewise, Zhu et al (2014) carried out separate GWAS in 2 populations, one population consisted of 820 Yorkshire pigs and Large White × Landrace intercrosses, and the other consisted of 208 Berkshire × Yorkshire F 2 intercrosses. Similarly, there were no overlapping significant SNPs identified in the 2 populations.…”
Section: Comparing the Single-population Analysis With The Combined Amentioning
confidence: 99%
“…For example, Qiao et al (2015) performed a GWAS using a White Duroc × Erhualian F 2 intercross population and a Chinese Sutai population to reveal SNP and candidate genes related to growth and fatness traits, but no overlap of results was found in the 2 populations. Likewise, Zhu et al (2014) carried out separate GWAS in 2 populations, one population consisted of 820 Yorkshire pigs and Large White × Landrace intercrosses, and the other consisted of 208 Berkshire × Yorkshire F 2 intercrosses. Similarly, there were no overlapping significant SNPs identified in the 2 populations.…”
Section: Comparing the Single-population Analysis With The Combined Amentioning
confidence: 99%
“…Several studies have reported QTLs and candidate genes to possibly identify functional mutations in different loci associated with backfat in pigs ( Fontanesi et al, 2012 ; Zhu et al, 2014 ; Pant et al, 2015 ). We have identified one strong candidate SNP (rs80985094) located on SSC5:66103958 with very strong association with backfat across populations.…”
Section: Discussionmentioning
confidence: 99%
“…The associated study results, such as identifying individual genes and large chromosomal segments obtained by different research groups, are often not entirely consistent with each other. This is due to several objective and subjective reasons: trait polygenicity, low marker effect values, the insufficient information content of traditional phenotypic measurements, the significant influence of paratype factors on the phenotype, which cannot always be taken into account, and the utilization of different models and approaches [13][14][15][16][17][18][19][20][21][22]. At the same time, other studies have identified the same candidate genes associated with trait variability in different animal species [23].…”
Section: Introductionmentioning
confidence: 99%